One‐lung ventilation in obese patients undergoing thoracoscopic lobectomy for lung cancer. Issue 3 (7th December 2022) - Leonardi, Beatrice; Forte, Stefano; Natale, Giovanni; Messina, Gaetana; Rainone, Anna; Opromolla, Giorgia; Puca, Maria Antonietta; Grande, Mario; Martone, Mario; Leone, Francesco; Fiorito, Roberta; Molino, Francesca; et al.
Abstract: Background: We evaluated the safety and feasibility of one‐lung ventilation in obese patients undergoing thoracoscopic lobectomy and whether obesity affected peri‐ and postoperative outcomes. Methods: This was a retrospective single center study including consecutive patients undergoing thoracoscopic lobectomy between October 2019 and February 2022. Obese patients were statistically compared to a control group to evaluate any differences in relation to one‐lung ventilation and peri‐ and postoperative outcomes. Results: Our study population included 111 patients; of these, 26 (23%) were included in the obese group, while 85 (77%) were included within the nonobese group. To obtain one‐lung ventilation in nonobese patients, a double‐lumen tube was more frequently used than a single‐lumen tube with bronchial blocker (61% vs. 39%; p  = 0.02), while in obese patients a single‐lumen tube with bronchial blocker was used more than a double‐lumen tube (81% vs. 19%, p  = 0.001). Intergroup comparison showed that a double‐lumen tube was the preferred method in nonobese patients, while a single‐lumen tube with bronchial blockers was the strategy of choice in obese patients ( p  = 0.0002). Intubation time was longer in the obese group than in the nonobese group (94.0 ± 6.1 vs. 85.0 ± 7.0 s; p  = 0.0004) and failure rate of first attempt at intubation was higher in the obese group (23% vs. 5%; p  = 0.01). Obesity was not associated with increased intra‐, peri‐ and postoperative complications and/or mortality. Conclusions: One‐lung ventilation is a feasible and safe procedure also in obese patients and obesity did not negatively affect peri‐ and postoperative outcomes after lung resection. Abstract : What is the best strategy to obtain one‐lung ventilation (OLV) in obese patients scheduled for thoracoscopic lung resections? Double lumen tubes (DLTs), (i.e., Carlens tube, Robertshaw tube etc…) or single‐lumen tube (SLT) with bronchial blockers (i.e., Univent, EZ blockers etc…)?Obese group compared to the control group was associated with: (i) higher use of a SLT with bronchial blockers than DLT; (ii) longer intubation time; and (iii) higher failure rate of intubation at the first attempt. No significant intergroup difference was found regarding intra‐, peri‐ and postoperative complications and/or mortality.OLV was also safely performed in obese patients, and obesity did not negatively affect surgical outcomes. The preoperative evaluation of patients remains crucial when choosing the best strategy for obtaining OLV.